Decoy-resistant IL18: how engineered E. coli enhances immune responses against tumors - Romee, Rizwan (Henry Stewart Talks, 2026)
Tumor microenvironment, Non-pathogenic Escherichia coli, Immune-activating cytokines, Live bacteria-based immunotherapeutic system, Anti-tumor responses